2017
DOI: 10.1016/j.scriptamat.2017.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the critical stress for the initiation of dynamic transformation in commercially pure titanium

Abstract: The dynamic transformation of alpha to beta is shown to take place in titanium at temperatures below the beta transus. The driving force for this transformation is the net softening associated with the formation of the lower flow stress beta phase. The obstacle to the transformation consists of the free energy difference between the phases as well as the work of dilatation during the phase change. Here the critical condition for transformation is defined as the moment when the driving force becomes equal to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 11 publications
(15 reference statements)
1
5
0
Order By: Relevance
“…Therefore, the critical strain (and stress) using this method is always higher than the actual initiation point. This was also discussed by the present authors in a previous paper [14], however, this work was focused in the occurrence of dynamic transformation in pure titanium. The present work will provide an alternative approach to calculate the critical stress in steels by using the free energy difference between the phases and the yield stress of freshly formed ferrite at elevated temperature.…”
Section: Introductionsupporting
confidence: 65%
“…Therefore, the critical strain (and stress) using this method is always higher than the actual initiation point. This was also discussed by the present authors in a previous paper [14], however, this work was focused in the occurrence of dynamic transformation in pure titanium. The present work will provide an alternative approach to calculate the critical stress in steels by using the free energy difference between the phases and the yield stress of freshly formed ferrite at elevated temperature.…”
Section: Introductionsupporting
confidence: 65%
“…It has been reported that the double differentiation technique overestimates the critical stress and strain since it requires the formation of about 5% of the dynamic phase in order for the operation of the softening mechanism to be detectable [37]. To overcome this barrier, the critical stresses are calculated by the total barrier energy method, which provides exact moment that transformation begins.…”
Section: Diffusion Analysis Of Alloying Elementsmentioning
confidence: 99%
“…Therefore, it is necessary to check the proportion of distortion energy in the free energy. The distortion energy [25]. If the reversal transformation occurs, the difference of ferrite flow stress and austenite yield stress will meet Eq.…”
Section: Reversal Austenizationmentioning
confidence: 99%
“…So, the influence of distortion energy on the transformation can be neglected, which is similar to the results reported in Refs. [25,29]. Therefore, the value of c is 265.93 MPa, based on Eqs.…”
Section: Reversal Austenizationmentioning
confidence: 99%